AKTIVITAS MAKAN ALAP-ALAP CAPUNG (MICROHIERAX FRINGILLARIUS DRAPIEZ, 1824) PADA MASA ADAPTASI DI KANDANG PENANGKARAN - Rachmatika, Rini (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTBlack thighed falconet is smallest bird from falconidae. This study aimed to determine nutrient requirement and describe feeding activity of black thighed falconet (Microhierax fringillarius Drapiez, 1824) on the adaptation period at the captive breeding facility. This observation was conducted at the bird captivity of Research Center of Biology. Black tighed falconet in this research have weighted about 33.65 ± 2.48 grams. Feed given once a day in the morning consist of scaly-breasted munia (Lonchura punctulata), mice, frozen tilapia fish and frozen beef. Observation of feeding activity using a focal animal sampling technique for 20 days. Data were analyzed descriptive method. Observations started in the morning at 08:00 am until feeding activity finished. Parameter measured were feeding activity, feed intake and feeding time needed. Temperature and humidity recorded in the morning (8:00 am), noon (12:00 pm), and afternoon (4:00 pm). Based on observations, the highest feed intake was mice (3,71 g/head/day) with a gross energy of 217.23 cal/head/day and the lowest was tilapia fish (2.52 g/head/days) with a gross energy of 147.52cal/head/day. The fastest meal time needed was mice (29.47±1.54 minutes) and the slowest was tilapia fish (46.51 ± 3.51 minutes). Keyword: Falconidae, feeding behavior, captive breeding